A Child with Chronic Fungal Infection in Bangladesh that Mimicked Malignancy: Disseminated Histoplasmosis - Khan, Eshita Reza; Jamal, Chowdhury Yakub; Karim, Anwarul; Nigar, Ismat; Diba, Farah (Bangladesh Journal of Child Health, 2018)
Histoplasma capsulatum is a dimorphic fungus, which primarily causes a pulmonary disease. It is found throughout the world with the soil being the environmental reservoir. In infants and toddlers, disseminated histoplasmosis is the commonest presentation. In this age group, 60-80% patients has acute disseminated progressive disease. Disseminated histoplasmosis may also cause bone involvement with osteolytic lesion. Here, we have described a rare and unusual disseminated histoplasmosis, a 3 and half year old boy from Bangladesh with multiple abscess like soft tissue lesions, along with multiple osteolytic bone lesions. Bangladesh J Child Health 2018; VOL 42 (2) :94-97